Late-onset Seizure and Left Hemiparesis after Unusual Craniocerebral Penetrating Injury by a Rusty Sickle: A Case Report - Sungkar, Affan Adib; Wijanarko, Ferry; Saadhi, Ikhdin; Alberta Setiawati, Dea (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Penetrating head injuries are a significant public health problem in worldwide, with an estimated 35.000 civilian deaths annually. Patients that survive to reach the hospital require rapid triage and imaging evaluation. This case report describes a patient with late-onset seizures and left hemiparesis after unusual craniocerebral penetrating injury by a rusty sickle. CASE PRESENTATION: A 26-year-old man reported that he had a sickle stabbed into the right-side parietal area. On admission, he had no neurological deficits. The rusty sickle was broken off just above the skull and did not protrude from the scalp. Computed tomography showed that the knife blade was in the parenchyma without underlying tract hematoma. Surgery was performed after 2 h of admission. Post-operatively, he recovered with no neurological deficit. After 16th days postoperatively, he was complaining of seizure and left hemiparesis. CT scan with contras showed edema and hypodense lesion at the right side of hemisphere. A course of intravenous phenytoin 100 mg/8 h and ceftriaxone 2 g/day was initiated. Physical therapy was done on the patient for 2 weeks. CONCLUSION: Traumatic brain injury (TBI) is the result of energy being transferred from an object to the human skull and underlying brain. Post-traumatic epilepsy is a common complication and can occur as early or late manifestations related to penetrating TBI. Prophylactic treatment of post-traumatic seizures (PTS) is currently not routinely recommended beyond 1 week following head injury (role of antiseizure prophylaxis). Phenytoin is the most rigorously tested AED for PTS.